STUDI AKUMULASI LOGAM BERAT KADMIUM (Cd) DAN EFEKNYA TERHADAP KANDUNGAN KLOROFIL DAUN MANGROVE Rhizophora mucronata - Dewi, Arum Rosita; Tri Nuraini, Ria Azizah; Yulianto, Bambang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
The condition of waters east of Semarang allegedly tainted by the many human activities such as 12th and December 11th in the waters of eastern pilula, Marcia hiantia, Placuna placenta, Paphia undulate, and Pharella javanic. The species with the highest abundance was Anadara granosa ( 301.1 Ind / ha (Station III)). Organic matter content was highest at station II, period 2, amounting to 22.56%, and lowest was at station V, period 3, amounting to 9.48%. The correlation between organic matter content of sediment with an abundance of bivalves in the waters of eastern Semarang overall resulted to receive Ho (no significant correlation).